2005
DOI: 10.1002/kin.20134
|View full text |Cite
|
Sign up to set email alerts
|

Chemical kinetic simulations behind reflected shock waves

Abstract: Chemical kinetic simulations that more accurately consider reaction conditions behind reflected shock waves in a high pressure shock tube have been conducted by accounting for (1) time-dependent temperature and pressure variations in contrast to assuming constant temperature and pressure, (2) the inclusion of reactions during quenching by cooling in contrast to the assumption of zero kinetic contributions, and (3) real gas behaviors in contrast to assuming ideal gas conditions. The primary objective of the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…The uncertainties in shock tube experiments are mainly associated with nonideality and measurement uncertainty. Tang and Brezinsky [28] have investigated the nonideal behavior in a 5.6 m long shock tube with an inner diameter of 50.8 mm, and found that the temperature increase due to pressure variation, ∆T 5 , can be up to 55 K at 2.5 MPa and 1 270 K. They concluded that for shock tube experiments with a less than 15% end wall pressure increase, the conventional treatment is suited to study chemical kinetics. A 0.5% uncertainty in shock wave velocity measurements results in about 1% and 2% experimental errors in temperature and pressure behind reflected shock waves in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The uncertainties in shock tube experiments are mainly associated with nonideality and measurement uncertainty. Tang and Brezinsky [28] have investigated the nonideal behavior in a 5.6 m long shock tube with an inner diameter of 50.8 mm, and found that the temperature increase due to pressure variation, ∆T 5 , can be up to 55 K at 2.5 MPa and 1 270 K. They concluded that for shock tube experiments with a less than 15% end wall pressure increase, the conventional treatment is suited to study chemical kinetics. A 0.5% uncertainty in shock wave velocity measurements results in about 1% and 2% experimental errors in temperature and pressure behind reflected shock waves in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluations of these potential effects via numerical simulations are the subject of this study 67 aimed to better characterize the UIC HPST.…”
Section: (F) Shock Tube Characterizationmentioning
confidence: 99%
“…Definition of governing boundary conditions -Constant pressure adiabatic isenthalpic system (Defines condition behind a reflected shock wave) The numerical techniques employed are described in more detail elsewhere 67,70 . The RG-Senkin developed as part of this study 67 was used to calculate the time dependent endwall temperature T 5 (t) obtained from the observed pressure traces P 5 (t) and the calibrated temperature T 5-avg in the time interval from when reflected shock wave arrives (reaction starts) to when the pressure drops to its 30% highest value. The reason we limit our efforts to this range is that all reactions stop within this range, a phenomena that will be demonstrated later in this article.…”
Section: (F) Shock Tube Characterizationmentioning
confidence: 99%
See 2 more Smart Citations